Richardson’s law and the origins of alcohol research - Snigdha Mukerjee; Cody A. Siciliano (Proceedings of the National Academy of Sciences, 2025)
Interest in the biological actions of alcohols, ethanol in particular, dates back to the earliest historical texts. Alcohol research is now a highly active field with roots in physiology, pharmacology, toxicology, and neuroscience. But at what point did interest and speculation evolve into bona fide science? Here, we set out to identify the earliest systematic empirical investigations into the biological actions of alcohols and unearthed a surprisingly rigorous literature which included a fundamental insight with significant implications for modern research and policy. Through manual backward citation mapping of archived texts, much of which was digitally inaccessible, we outline the origins of alcohol research beginning with a transcribed lecture from Benjamin Ward Richardson in 1869. In the years immediately following, the field of alcohol research was legitimized around what came to be briefly known as “Richardson’s law.” Richardson’s law states that the acute toxicity of straight-chain monohydroxy alcohols is directly proportional to the carbon chain length of the molecule. This law was recognized only briefly not because it was disproven, but rather because it was simply forgotten during the decades that passed between its inception and the advent of systematic bibliographic databases which paved the way for digital archiving. Quantitative analysis of studies spanning a century revealed that across monohydroxy alcohols with one (methanol) to thirteen (tridecanol) carbons, there is a near-deterministic relationship between chain-length and lethal dose (R 2 = 0.96). Richardson’s law of alcohol potency has silently stood the test of time and is among functional biology’s oldest and least challenged scientific laws.